Opening new schools under current admission procedure: problems and options - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2020)
Using data from a representative cluster survey, the author concludes that the possibility to open new BRAC schools under current admission procedure would be difficult because of the lack of adequate number of children. Findings reveal that only 16.7 percent children a~ed 6-15 are out-of-school. Among them, the proportion of girls is less (13.9%) than boys (19.2%). Of the two models, BRAC will face more difficulty in getting students for NFPE than BOEC. The author suggests that the current admission policy be revised to include younger (<8 years) and boys, and the children of socioeconomically better off sections of the community.